2000
DOI: 10.1302/0301-620x.82b1.9694
|View full text |Cite
|
Sign up to set email alerts
|

Graded compression stockings in elective orthopaedic surgery

Abstract: We recruited 89 patients who had hip or knee replacements to assess the performance of below-knee graded compression stockings. The pressure gradients generated by the stockings were measured and all patients had venography of the ipsilateral leg. We found that 98% of stockings failed to produce the 'ideal' pressure gradient (+/- 20%) of 18, 14 and 8 mmHg from the ankle to the knee, while 54% produced a 'reversed gradient' on at least one occasion during the course of the study. The overall rate of deep-venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In this study, we found that not all tested compression stockings have the claimed pressure gradients, which agrees with the results from other studies. 17,25,26 Although all tested GCSs exerted the negative pressure gradients from ankle to thigh level, the calf pressures applied by some GCSs with moderate and high pressure classes were 88.1 to 93.3% of their ankle pressures, which was much higher than the specifications of the European standards. This could be related to a number of factors.…”
Section: Pressure Gradientsmentioning
confidence: 85%
See 2 more Smart Citations
“…In this study, we found that not all tested compression stockings have the claimed pressure gradients, which agrees with the results from other studies. 17,25,26 Although all tested GCSs exerted the negative pressure gradients from ankle to thigh level, the calf pressures applied by some GCSs with moderate and high pressure classes were 88.1 to 93.3% of their ankle pressures, which was much higher than the specifications of the European standards. This could be related to a number of factors.…”
Section: Pressure Gradientsmentioning
confidence: 85%
“…This might be one of the reasons for recurrence of venous ulceration even if the patients did wear their elastic compression stockings. 16,17 In recent studies, Best and colleagues found that 98% of the compression stockings tested failed to produce the ideal pressure gradient and more than half produced a tourniquet effect, which was associated with a significantly higher incidence of deep venous thrombosis. 17 Meanwhile, the exact mechanisms of action of GCSs remain controversial, if not unclear.…”
Section: The Research Grant Council Provided Funding For This Researcmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, excessive ankle interface pressures could cause skin necrosis and thrombosis. [7][8][9] In the international literature, a large range of pressures are reported to be effective. Lower pressures (10-30 mmHg) are said to be sufficient after sclerotherapy of telangiectasias, in symptomatic varicose veins including those associated with pregnancy, and for the prevention of edema and deep venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Band-like constrictions due to compression therapy can increase the risk of deep vein thrombosis. 9 Whereas the quality of a compression bandage depends on the experience and skill of the bandager, 10 patients should be able to easily use optimally fitted compression stockings, which should always exert their effects optimally on the affected leg.…”
mentioning
confidence: 99%